2021
DOI: 10.1186/s12903-021-01678-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual reality distraction on pain and anxiety during infiltration anesthesia in pediatric patients: a randomized clinical trial

Abstract: Background Different distraction techniques have been used in dentistry and have shown great results in managing anxious pediatric patients specially during local anesthesia administration. One of the recently invented techniques is virtual reality. The purpose of the study was to evaluate the effect of virtual reality distraction on anxiety and pain during buccal infiltration anesthesia in pediatric patients. Methods Healthy, cooperative 6- to 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 28 publications
0
54
0
1
Order By: Relevance
“…The patient's inability to see the dental practitioner and instruments may be one advantage of VR. The effectiveness of VR distraction treatment may depend on how patients feel in the virtual environment [49]. For this reason, video stimulation and audio simulation may be detrimental in making the users' experience more immersive and by trying to decrease the dental pain [8].…”
Section: Applications In Dental Phobiamentioning
confidence: 99%
“…The patient's inability to see the dental practitioner and instruments may be one advantage of VR. The effectiveness of VR distraction treatment may depend on how patients feel in the virtual environment [49]. For this reason, video stimulation and audio simulation may be detrimental in making the users' experience more immersive and by trying to decrease the dental pain [8].…”
Section: Applications In Dental Phobiamentioning
confidence: 99%
“…The characteristics of all the studies included are reported in Table 2. Out of 10 incoming studies, 3 studies (30%) in Korea [2,24,25] and other studies in Brazil [19], Iran [20], Netherlands [21], Saudi Arabia [22], Republic of Korea [1], Spain [23] and China [3]. Studies in two categories of randomized trial (20%) [21,24] and randomized clinical trial (60%) [1-3, 19, 20, 22, 23, 25] Were classified.…”
Section: Characteristics Of the Studymentioning
confidence: 99%
“…However, in one study, virtual reality was used as an educational tool [1]. In 3 cases (30%) reduction of anxiety in the two groups of control and intervention was not significantly different [19,21,22]. In all studies, the control group received routine care, including routine behavior management techniques and anxiety control pills.…”
Section: The Effects Of Virtual Reality On Children's Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recent literature has shown that video demonstration is very effective to improve student confidence in psychomotor skills. 6,7 Real-time virtual reality learning experience has been introduced as an educational tool to enhance the clinical learning of students. 8 Contextually, learners in dental school deliver their first injection directly on patients under supervision of teachers to reduce patients anxiety and build confidence.…”
mentioning
confidence: 99%